Interaction Between Marine Fauna and the Small Pelagic Fishery in the Coastal Environment of the Gulf of California, Mexico - Morales-Bojórquez, Enrique; Nevárez-Martínez, Manuel O.; García-Alberto, Gabriela; Villalobos, Héctor; Aguirre-Villaseñor, Hugo; Larios-Castro, Estefani; González-Peláez, Sergio S.; Arizmendi-Rodríguez, Dana I.; Martínez-Zavala, María de los Ángeles (Frontiers in Marine Science, 2021)
The first steps have been taken to analyze the effects of small pelagic harvests on the Gulf of California ecosystem. The primary goal of this study was to estimate the latitudinal differences in regionalized baselines of endangered and threatened marine species attracted to a purse seine in a Mexican fishery of small pelagic fish. We also analyzed the spatial patterns in fishing effort in the Gulf of California. Seven zones were analyzed in the Gulf of California, including the east and west coasts, and a total of 3,051 fishing sets were analyzed during January 2013 and July 2014; the data provided a comprehensive picture of the distribution of the fishing effort, small pelagic fishes harvested, and the presence of species attracted to the fishing sets. The region in the upper Gulf of California showed a low presence of individuals, and the east coast recorded more sightings than the west coast; consequently the fishing effort was mainly distributed in the east coast. The number of individuals for several species sighted and counted by fishing set was used for each zone in the Gulf of California, and a conservative baseline based on the Pennington estimator was computed. It provided an average value of endangered and threatened marine species attracted to a purse seine for each zone. The Pennington estimator is recommended due to the precision of the confidence intervals and the nature of the uncertainty in the data collection based on sightings.